Bamboo for Riverbanks Rehabilitation and Economy Empowerment of Local Community of Pitu Village, Pitu Subdistrict, Ngawi Regency, East Java - Winastuti Dwi Atmanto; Eny Faridah; Ananto Triyogo; Aqmal Nur Jihad; Sawitri Sawitri (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2023)
Pitu Village, Pitu subdistrict located along the Bengawan Solo River in Ngawi, East Java, is one of the regions with a high risk of flooding due to human activities like as settlement and intensive agriculture along the riverbanks. This phenomena causes soil erosion and crop failure, which reduces the income of the Pitu local community. A rehabilitation strategy is required to resolve this issue, not only for the recovery of the riverbanks but also for the enhancement of the local community’s revenue. The objective of this community activity is to educate the public about the use of bamboo species in riverbank restoration (Dendrocalamus asper). Bamboo is selected because it has both ecological and socioeconomic benefits. This project was conducted between March and September of 2022 on the Grojogan riverbanks, Bengawan Solo River, Pitu Village, and Pitu Subdistrict. This exercise utilized Focus Group Discussion, lecture, and practice or training as its methods. The population of Desa Pitu might simply adopt bamboo species and cultivate them along riverbanks. The community and the community service team from the Silviculture Department planted 1,000 bamboo seedlings. The survival rate of bamboo plantations exceeded eighty percent, and new shoots grew swiftly (5–15 cm for 5 months). Training in bamboo growing and bamboo product processing improved their skills well. The community generates bamboo seedlings successfully through vegetative propagation. In addition, three local communities in Cebongan, Sleman, and Yogyakarta participated in a four-day bamboo processing training program. They were also producing some tables, chairs, and handicrafts with success (woven bamboo).